2017
DOI: 10.1002/ece3.3686
|View full text |Cite
|
Sign up to set email alerts
|

Proximate causes of altitudinal differences in body size in an agamid lizard

Abstract: Body size is directly linked to key life history traits such as growth, fecundity, and survivorship. Identifying the causes of body size variation is a critical task in ecological and evolutionary research. Body size variation along altitudinal gradients has received considerable attention; however, the underlying mechanisms are poorly understood. Here, we compared the growth rate and age structure of toad‐headed lizards (Phrynocephalus vlangalii) from two populations found at different elevations in the Qingh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 68 publications
(102 reference statements)
2
43
1
1
Order By: Relevance
“…Consistent with our prediction, potential prey availability was more abundant at the high-elevation site than at the low-elevation site, and high-elevation juveniles grew faster than low-elevation ones. Actually, higher growth rates for high-elevation P. vlangalii were also confirmed in another study using field mark-recapture data and von Bertalanffy growth parameters [ 39 ]. As suggested by some previous studies, the effect of food availability on lizard growth rate is more immediate [ 27 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Consistent with our prediction, potential prey availability was more abundant at the high-elevation site than at the low-elevation site, and high-elevation juveniles grew faster than low-elevation ones. Actually, higher growth rates for high-elevation P. vlangalii were also confirmed in another study using field mark-recapture data and von Bertalanffy growth parameters [ 39 ]. As suggested by some previous studies, the effect of food availability on lizard growth rate is more immediate [ 27 ].…”
Section: Discussionmentioning
confidence: 56%
“…The Qinghai toad-headed lizard ( Phrynocephalus vlangalii ), which is widely distributed in the Qinghai-Tibetan Plateau with an elevation range from 2000 to 4500 m, provides an excellent model to study altitudinal variation of growth rate in reptiles. Our previous study indicated that P. vlangalii individuals at a high-elevation site (Maduo, 4250 m elevation) can grow faster and reach a larger adult size than those at a low-elevation site (Maqu, 2930 m elevation) [ 39 ]. In this study, we conducted a mark-recapture experiment in the field and a common-garden experiment in the laboratory to determine genetic vs environmental components of this between-population difference in juvenile growth rate.…”
Section: Introductionmentioning
confidence: 99%
“…As the changeable plateau climate and low environmental temperature allyear-round, it is difficult for reptile species from different populations to keep similar body temperature. Meanwhile, combined with a high food abundance at high altitude (Lu, Xu et al 2018), the P. vlangalii living at Maduo selected a relatively low body temperature may be more conducive to improving the efficiency of energy utilization and may conduce to allocate more energy on territories occupied, mating, avoiding predator and predation (Gvoždík 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The parameters L ∞ (asymptotic SVL) and k, and their asymptotic confidence intervals (CI), were estimated by means of a non-linear regression procedure using the IBM SPSS 21.0 software program. Then, the growth rates were calculated as R = k(L ∞ − L t ) (Bülbül et al, 2016a;Lu et al, 2017). The growth curves were considered to be significantly different if the 95% confidence intervals of the growth coefficient k did not overlap (James, 1991;Wapstra et al, 2001).…”
Section: Methodsmentioning
confidence: 99%